Social Proxies and Real-World Avatars: Impersonation as a Mode of Capitalist Production. - LaFarge, Antoinette (Art Journal)
An essay is presented which discusses artists' use of impersonation and proxies in the art industry, including the impact that the capitalist mode of production in which artists are their own managers has on this phenomenon. An overview of artists' use of pseudonyms, including so as to conceal their identities, is provided.